Alternative liquid dielectrics in power transformer insulation: a review - Bokang Agripa Tlhabologo; Ravi Samikannu; Modisa Mosalaosi (Institute of Advanced Engineering and Science, 2021)
Transformer liquid dielectrics evolved where mineral oil has been the dominant choice until emergence of synthetic esters and natural esters. Natural ester-based oils have been under extensive investigations to enhance their properties for replacing petroleum-based mineral oil, which is non-biodegradable and has poor dielectric properties. This paper focuses on exposition of natural ester oil application in mixed transformer liquid dielectrics. Physical, chemical, electrical, and ageing characteristics of these dielectrics and the dissolved gas analysis (DGA) were reviewed. Physical properties include viscosity, pour point, flash and fire point which are vital indicators of heat insulation and fire risk. Chemical properties considered are water content, acid number, DGA, corrosive sulphur, and sludge content to limit and detect degradation and corrosion due to oil ageing. Electrical properties including breakdown voltage were considered for consistent insulation during overload and fault conditions. These properties of evolving alternative dielectrics were reviewed based on ASTM International standards and International Electro technical Commission standards for acceptable transformer liquid dielectrics. This review paper was compiled to avail modern methodologies for both the industry and scholars, also providing the significance of using mixed dielectrics for power transformers as they are concluded to show superiority over non-mixed dielectrics.